Pengaruh Brand Image, Brand Awareness, Brand Trust terhadap Brand Loyalty Melalui Kepuasan Konsumen Sebagai Variabel Intervening pada Pelanggan Produk Kecantikan Wardah: Studi pada Mahasiswa FISIP Universitas Pembangunan Nasional “Veteran” Jawa Timur - Aristanti Prihatini, Dini; Jojok Dwiridotjahjono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study investigates the relationship between brand image, brand awareness, brand trust, customer satisfaction, and brand loyalty concerning Wardah beauty products. Data were obtained from several previous studies conducted on similar products. Various analyses were conducted on respondent responses and processed using statistical techniques. The research results indicate that brand image, brand awareness, and brand trust have a significant positive influence on customer satisfaction with Wardah products. Furthermore, customer satisfaction also has a significant positive impact on brand loyalty. It means that the better the brand image, brand awareness, and brand trust of Wardah, the higher the level of customer satisfaction with the products. This, in turn, affects consumer loyalty to the Wardah brand. From this research, it can be concluded that brand image, brand awareness, and brand trust significantly affect customer satisfaction, which, in turn, significantly contributes to brand loyalty. In the context of Wardah beauty products, customer satisfaction becomes an essential factor that bridges the influence of brand image, brand awareness, and brand trust on consumer loyalty to the products. This study aids in understanding the complex relationship between key factors in building brand loyalty for Wardah beauty products.